Effect of low‐intensity extracorporeal shockwave therapy on nocturnal penile tumescence and rigidity and penile haemodynamics. (21st July 2020) - Huang, Yan‐Ping; Liu, Wei; Liu, Yi‐Dong; Zhang, Ming; Xu, Shi‐Ran; Lu, Mu‐Jun
Abstract: The study aims to evaluate the effect of low‐intensity extracorporeal shockwave therapy (Li‐ESWT) on nocturnal erection and penile haemodynamics. Patients with erectile dysfunction (ED) were enrolled from January 2018 to March 2019. Self‐reported erectile symptoms, the International Index of Erectile Function‐5 (IIEF‐5) and Erection Hardness Scores (EHS), nocturnal penile tumescence and rigidity (NPTR) and cavernous duplex Doppler ultrasound (CDDU) were evaluated. NPTR and CDDU were evaluated by Rigiscan and vascular ultrasound system respectively. Comparisons of NPTR and CDDU parameters were performed before and after Li‐ESWT (Renova, once a week, 4 weeks in total). A total of 35 cases (mean age 36.51 ± 11.47 years) were enrolled for analysis. The IIEF‐5 (10.60 ± 5.99 vs. 15.13 ± 6.22, p  = .003), EHS ( p  = .016) and self‐reported erectile hardness ( p  = .014) were significantly improved after 1‐month treatment. Nocturnal erection frequency ( p  = .010), duration of total erection ( p  = .017), duration of erectile rigidity ≥60% at penile tip and base ( p  = .014 and p  = .002) and the best erectile rigidity at penile tip and base ( p  = .012 and p  = .005) improved significantly after treatment. However, no CDDU parameters improved after Li‐ESWT (all p  > .05). Li‐ESWT can effectively improve subjective erectile function and nocturnal erection in ED patients. Large sample and well‐designed studies need to be developed for supporting the current findings.